The Development of Company Profile Website for CV. Rian using Waterfall Model SDLC - Irma Amelia Dewi; Lisye Fitria; Arie Desrianty; Alif Ulfa Afifah; M. Faishal Dzaky (Institut Teknologi Nasional, Bandung, 2020)
Nowadays, the benefits of using the internet can be felt in society or even in the industrial world, either for business or just for entertainment purposes. Until 2017, Indonesia is one of the countries with the highest internet users globally, with around 112,6 million internet users. On the other hand, many small businesses have not used the internet to advertise their products. This project's main objective is to design and develop a company profile website of CV Rian as one of the brick micro-industry in Nagrek, West Java, enabling people to search and access information easily and quickly. This project uses Waterfall Model as Sofware Development Life Cycle (SDLC), MySQL as the database, and PHP for server-side scripting. The database is used for storing posts, admin data, and images.